Strategies for implementing integrated marketing communications - Percy, Larry (Lincolnwood, Ill. : NTC Business Books, 1997)
This book is about: Overview of integrated marketing communications; Initial IMC planning considerations; IMC planning tools; Integrating advertising and promotion; Selecting promotion tactics; ...
Keywords: Marketing; Management; Communication in marketing